STRUKTUR HISTOLOGI TRAKEA TIKUS PUTIH (Rattus sp.) YANG TERPAPAR ASAP ROKOK SETELAH DIBERI EKSTRAK BUAH JUWET (Syzygium cumini L.) - Angga Kristiawan, I Komang; Rai Suarni, Ni Made; Yulihastuti, Dwi Ariani (SIMBIOSIS, 2017)
This study aimed to determine the effect of juwet fruit extract on histological structure of rat( Rattus sp)  trachea which exposed to cigarette smoke. This research used Completely Randomized Design (CRD), with four treatments: the control group (K 0 ) treated with 0.5 % CMC–Na, (K 1 ) group is exposed to cigarette smoke, (K 2 ) group were given juwet fruit extract, and (K 3 ) group is exposed to cigarette smoke and juwet fruit extracts. Each treatment consisted of 6 rats as replication. The exposure to cigarette smoke is given from  an aerator pump lit cigarettes. Juwet fruit extract and 0.5 % CMC - Na was orally administered (gavage method) for 48 days. The existence of comperative descriptive observed cilia. And goblet number, high epithelium and lumen diameter Data were analyzed with ANOVA and If they were 5 % significantly different would be followed by Duncan test. Results showed that the extract of the fruit juwet significant effect on the histological structure of the trachea mice that had been exposed to smoke.